Sex and diet-dependent gene alterations in human and rat brains with a history of nicotine exposure - Vargas-Medrano, Javier; Carcoba, Luis M.; Vidal Martinez, Guadalupe; Mulla, Zuber D.; Diaz, Victoria; Ruiz-Velasco, Alejandra; Alvarez-Primo, Fabian; Colina, Gabriela; Iñiguez, Sergio D.; Thompson, Peter M.; O’Dell, Laura E.; Gadad, Bharathi S. (Frontiers in Psychiatry, 2023)
Chronic nicotine exposure induces changes in the expression of key regulatory genes associated with metabolic function and neuronal alterations in the brain. Research comparing pre-clinical models with human subjects provides an important opportunity to understand common biomarkers of the harmful effects of nicotine as well as information that may help guide the development of more effective interventions for nicotine cessation. Human postmortem dorsolateral prefrontal cortex (DLPFC) tissue BA9 was collected from female and male subjects, smokers and non-smokers (N=12 per group). Rat frontal lobes were collected from female and male rats that received a regular diet (RD) or a high-fat diet (HFD) (N=12 per group) for 14 days following implantation of an osmotic pump (Alzet) that delivered nicotine continuously. Controls received a sham surgical procedure. RNA was extracted from tissue from human and rat samples and reversed-transcribed to cDNA. Gene expression of CHRNA10, CERKL, SMYD1, and FA2H in humans was compared to rats in each subset of groups and quantified by qPCR methods. Additionally, protein expression of SYMD1 was observed by IHC in human DLPFC (BA9). Humans with a history of smoking displayed decreased CHRNA10 (p=0.0005), CERKL (p=<0.0001), and SMYD1 (p=0.0005) expression and increased FA2H (p=0.0097) expression compared to nonsmokers (p<0.05). Similar patterns of results were observed in nicotine exposed versus control rats. Interestingly, sex-related differences in gene expression for CERKL and FA2H were observed. In addition, ANCOVA analysis showed a significant effect of nicotine in a sex-different manner, including an increase in CERKL in male and female rats with RD or HFD. In rats exposed to an HFD, FA2H gene expression was lower in nicotine-treated rats compared to RD rats treated with nicotine. These results suggest that a history of long-term nicotine exposure in humans alters the expression of sphingolipid metabolism-related (CERKL, SMYD1, and FA2H) and neuronal (CHRNA10) marker genes compared to rats. Sex- and diet-dependent differences appear in nicotine-exposed rats, critical in regulating sphingolipid metabolism and nicotinic acetylcholine receptors. This research enhances the construct validity of rat models of nicotine dependence by showing a similar pattern of changes in gene expression in human subjects with a smoking history.